Bisphosphonate's and Intermittent Parathyroid Hormone's Effect on Human Spinal Fusion: A Systematic Review of the Literature - Stone, Michael A. (Asian Spine J, 2017)
There has been a conscious effort to address osteoporosis in the aging population. As bisphosphonate and intermittent parathyroid hormone (PTH) therapy become more widely prescribed to treat osteoporosis, it is important to understand their effects on other physiologic processes, particularly the impact on spinal fusion. Despite early animal model studies and more recent clinical studies, the impact of these medications on spinal fusion is not fully understood. Previous animal studies suggest that bisphosphonate therapy resulted in inhibition of fusion mass with impeded maturity and an unknown effect on biomechanical strength. Prior animal studies demonstrate an improved fusion rate and fusion mass microstructure with the use of intermittent PTH. The purpose of this study was to determine if bisphosphonates and intermittent PTH treatment have impact on human spinal fusion. A systematic review of the literature published between 1980 and 2015 was conducted using major electronic databases. Studies reporting outcomes of human subjects undergoing 1, 2, or 3-level spinal fusion while receiving bisphosphonates and/or intermittent PTH treatment were included. The results of relevant human studies were analyzed for consensus on the effects of these medications in regards to spinal fusion. There were nine human studies evaluating the impact of these medications on spinal fusion. Improved fusion rates were noted in patients receiving bisphosphonates compared to control groups, and greater fusion rates in patients receiving PTH compared to control groups. Prior studies involving animal models found an improved fusion rate and fusion mass microstructure with the use of intermittent PTH. No significant complications were demonstrated in any study included in the analysis. Bisphosphonate use in humans may not be a deterrent to spinal fusion. Intermittent parathyroid use has shown early promise to increase fusion mass in both animal and human studies but further studies are needed to support routine use.